Một số ý kiến về lồng ghép vấn đề biến đổi khí hậu trong hoạch định chính sách phát triển theo hướng bền vững ở nước ta - Nguyễn, Danh Sơn (Trung tâm Nghiên cứu Tài nguyên và Môi trường, 2016)
Climate Change (CC) is first an environmental problem. The impacts of CC are large and comprehensive, especially on the lives of poor people whose livelihoods depend on nature. Under the impact of CC, nature is experiencing major changes, even deformations, preventing the environment from being able to carry out its normal functions. It is forecasted that Vietnam will be one of the five countries most impacted by CC, and these impacts will be felt widely throughout the country, including in the Red River and Mekong deltas, the northern and central highlands and the central and southern coastal regions. Vietnam understands the threat posed by CC on the sustainable development process and the Prime Minister has recently promulgated (2 December 2008) the National Target Program to respond to Climate Change, which indicates that “the tasks to respond to climate change must be integrated into development strategies, programmes, plans and planning in all sectors and at all levels” and ministries, sectors and localities are asked to integrate CC issues into their socio-economic development strategies, master plans and other plans. This report is presented in two parts: the first part describes briefly a picture of CC in Vietnam based on the recent scenario announced by MONRE, with initial identification of CC impacts, which serves as background for the second part giving some recommendations on integrating CC issues into policy-making toward sustainability in Vietnam in the coming period.